2007
DOI: 10.1016/j.neuroimage.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Integrating VBM into the General Linear Model with voxelwise anatomical covariates

Abstract: A current limitation for imaging of brain function is the potential confound of anatomical differences or registration error, which may manifest via apparent functional "activation" for between-subject analyses. With respect to functional activations, underlying tissue mismatches can be regarded as a nuisance variable. We propose adding the probability of gray matter at a given voxel as a covariate (nuisance variable) in the analysis of voxelwise multisubject functional data using standard statistical techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(197 citation statements)
references
References 34 publications
4
193
0
Order By: Relevance
“…Visual examination of the fMRI and VBM results showed that the differences between the MCI and HC groups were in different regions for the two modalities. A more detailed analysis integrating the two modalities is necessary, such as performed by Oakes and colleagues [71], to make statements about the possible interaction between brain activation and GM density.…”
Section: Discussionmentioning
confidence: 99%
“…Visual examination of the fMRI and VBM results showed that the differences between the MCI and HC groups were in different regions for the two modalities. A more detailed analysis integrating the two modalities is necessary, such as performed by Oakes and colleagues [71], to make statements about the possible interaction between brain activation and GM density.…”
Section: Discussionmentioning
confidence: 99%
“…To correct for atrophy, partial volume information of grey matter was estimated and maps for all participants were created based on the T1-weighted images using the FSL script feat gm prepare. These maps were added as voxelwise explanatory variable in the GLM design [73]. Demeaned age and depression scores were entered as covariates of no interest.…”
Section: Data Preprocessing On Group Levelmentioning
confidence: 99%
“…Also, the integration of complementary information through a multimodal approach will be very useful to overcome the shortcomings of each single protocol, requiring advanced analysis tools which are able to integrate information from different protocols into the same processing pipeline. Similar approaches are likely to aid in better discrimination and staging of AD [8,[246][247][248]. In this context, information from different modalities may be simultaneously combined using the support of machine learning algorithms enabling the classification of a single subject into a predefined group while dealing with any type of input features (e.g.…”
Section: Functional Mri Markersmentioning
confidence: 99%